The icon and the square : Russian modernism and the Russo-Byzantine revival - Taroutina, Maria (The Pennsylvania State University Press, 2018)
"Charts the rediscovery and rigorous reassessment of the medieval Russo-Byzantine artistic tradition in Russia in the years 1860-1920. Explores the link between Byzantine revivalism and modernist experimentation, which ultimately made a significant and lasting impact on twentieth-century avant-garde movements"--Provided by publisher